Colour, culture and difference in Australian teacher education: voices from the edge. (24th July 2019) - Joseph, Dawn; Johnson, Richard
Abstract : Purpose: Although much has been written about international students in higher education in Australia, there is a paucity of research and discussion about international academics especially non-whites and their lived experience in the workplace. This paper represents the voices of two academics working in metropolitan universities in Melbourne. The purpose of this paper is to raise awareness of how in spite of all the goodwill and highbrow research, the "corridors of academia" need to be examined in considering the politics of inclusion and internationalisation as the authors still need to address issues of colour as they exist in the academy. Design/methodology/approach: The authors use narrative inquiry and reflection to tell the story as both phenomenon and method where the phenomenon is the story and inquiry is the narrative. Findings: The findings suggest student and staff perceptions of difference are mostly theorised but not practiced within the academy. Research limitations/implications: The paper includes two voices, a limitation in itself, thus generalisations cannot be made to other academics or institutions. The authors recommend more professional development for staff and students alike to embrace issues of colour, culture and difference. Practical implications: The authors draw attention to the need for academics to reflect on their behaviour within their own academic communities and be more aware of minority groups in academia. Social implications: By including and listening to issues facing minority groups (academics and students) can only improve the social cohesion of university worksites. Originality/value: This is an original work carried out by both authors. It raises concerns that may also be experienced international staff and or students.